How Water and Ion Mobility Affect the NMR Fingerprints of the Hydrated JBW Zeolite: A Combined Computational‐Experimental Investigation. Issue 68 (10th October 2022) - Vanlommel, Siebe; Hoffman, Alexander E. J.; Smet, Sam; Radhakrishnan, Sambhu; Asselman, Karel; Chandran, C. Vinod; Breynaert, Eric; Kirschhock, Christine E. A.; Martens, Johan A.; Van Speybroeck, Veronique
Abstract: An important aspect within zeolite synthesis is to make fully tunable framework materials with controlled aluminium distribution. A major challenge in characterising these zeolites at operating conditions is the presence of water. In this work, we investigate the effect of hydration on the 27 Al NMR parameters of the ultracrystalline K, Na‐compensated aluminosilicate JBW zeolite using experimental and computational techniques. The JBW framework, with Si/Al ratio of 1, is an ideal benchmark system as a stepping stone towards more complicated zeolites. The presence and mobility of water and extraframework species directly affect NMR fingerprints. Excellent agreement between theoretical and experimental spectra is obtained provided dynamic methods are employed with hydrated structural models. This work shows how NMR is instrumental in characterising aluminium distributions in zeolites at operating conditions. Abstract : Discovering the aluminium location is a challenging endeavour in zeolites, as overlapping resonances complicate spectral assignment. Combining theoretical and experimental NMR is indispensable in spectral interpretation while the inclusion of configurationally diverse water molecules is essential.